The macrophage scavenger receptor type A is expressed by activated macrophages and protects the host against lethal endotoxic shock. - Haworth, R; Platt, N; Keshav, S; Hughes, D; Darley, E; Suzuki, H; Kurihara, Y; Kodama, T; Gordon, S (1997)
During gram-negative bacterial infections, lipopolysaccharide (LPS) stimulates primed macrophages (Mphi) to release inflammatory mediators such as tumor necrosis factor (TNF)-alpha, which can cause hypotension, organ failure, and often death. Several different receptors on Mphi have been shown to bind LPS, including the type A scavenger receptor (SR-A). This receptor is able to bind a broad range of polyanionic ligands such as modified lipoproteins and lipoteichoic acid of gram-positive bacteria, which suggests that SR-A plays a role in host defense. In this study, we used mice lacking the SR-A (SRKO) to investigate the role of SR-A in acquired immunity using a viable bacillus Calmette Guérin (BCG) infection model. We show that activated Mphi express SR-A and that this molecule is functional in assays of adhesion and endocytic uptake. After BCG infection, SRKO mice are able to recruit Mphi to sites of granuloma formation where they become activated and restrict BCG replication. However, infected mice lacking the SR-A are more susceptible to endotoxic shock and produce more TNF-alpha and interleukin-6 in response to LPS. In addition, we show that an antibody which blocks TNF-alpha activity reduces LPS-induced mortality in these mice. Thus SR-A, expressed by activated Mphi, plays a protective role in host defense by scavenging LPS as well as by reducing the release by activated Mphi of proinflammatory cytokines. Modulation of SR-A may provide a novel therapeutic approach to control endotoxic shock.